2018
DOI: 10.1021/jacs.8b10793
|View full text |Cite
|
Sign up to set email alerts
|

Ag Nanocrystals with Nearly Ideal Optical Quality: Synthesis, Growth Mechanism, and Characterizations

Abstract: Though Ag nanocrystals are predicted to be the best material for localized surface plasmon resonances (LSPR) in the visible light region, realization of their ideal LSPR properties is hindered by the stringent requirements: i.e., simultaneous control of their size, shape, crystallinity, and surface structure. To achieve this goal, a synthetic scheme in non-polar solvent coupled with mild oxidative etching by H + ions has been established. With a trace amount of Cl − ions as catalysts, H + ions (in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…The peak intensity at 34° was enlarged in Ag 2 Te@Ag 2 S QDs, indicating the formation of Ag 2 S. In the case of Ag 2 Te QDs with emission peak at 1524 nm as the core, the photoluminescence peak of Ag 2 Te@Ag 2 S QDs got a slight red‐shift to 1560 nm (Figure 4e). This was derived from the extra Ag precursor in the reaction which would be readily adsorbed onto the surface of Ag 2 Te in the nonpolar solvent, [ 42 ] resulting the increase of Ag 2 Te core to give the red‐shift of the photoluminescence. Meanwhile, the adsorbed Ag ions also induced new traps on the surface, leading to the reduction of its photoluminescence intensity (Figure S10, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…The peak intensity at 34° was enlarged in Ag 2 Te@Ag 2 S QDs, indicating the formation of Ag 2 S. In the case of Ag 2 Te QDs with emission peak at 1524 nm as the core, the photoluminescence peak of Ag 2 Te@Ag 2 S QDs got a slight red‐shift to 1560 nm (Figure 4e). This was derived from the extra Ag precursor in the reaction which would be readily adsorbed onto the surface of Ag 2 Te in the nonpolar solvent, [ 42 ] resulting the increase of Ag 2 Te core to give the red‐shift of the photoluminescence. Meanwhile, the adsorbed Ag ions also induced new traps on the surface, leading to the reduction of its photoluminescence intensity (Figure S10, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…Recently, conceptually new entropic ligands were introduced 8,13 , which can boost the solubility of nanocrystal-ligand complexes and enables the large-scale printing of electronics and optoelectronics 14 . Importantly, entropic ligands are identified as a general solution for achieving excellent solubility of nanocrystals with diverse inorganic composition 14,15 , which plays a decisive role in both synthesis and processing 16,17 . For instance, by simply mixing two common n -alkanoate ligands with distinguishable hydrocarbon-chain lengths, solubility of the resulting nanocrystal-ligands complexes could increase up to ~6 orders of magnitude in comparison with either of pure-ligand counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this work suggested that it is possible to construct a plasmonic absorber that absorbs light uniformly throughout the solar spectrum by designing an appropriate Au and/or Ag architecture (mixture or tandem). Due to the good plasmonic properties of composites, many strategies have been applied to synthesize well‐defined plasmonic nanostructures such as spheres, [ 223 ] rods, [ 224 ] cubes, [ 225 ] disks, [ 226 ] dimers/trimers, [ 227 ] stars, [ 228 ] plates, [ 229 ] and dodecahedrons. [ 230 ] Lee and co‐workers vacuum deposited Au onto a polymer template and released it from the substrate to form a monodisperse 2D nanodisk.…”
Section: Applicationsmentioning
confidence: 99%
“…On the other hand, the excitation of the SPR of noble‐metal composites results in the amplification of local electromagnetic fields, a process also known through the observation of surface‐enhanced Raman scattering (SERS). [ 48,223,231,232 ] The sensitivity of SERS primarily depends on electromagnetic “hotspots” where the local electric field is extremely intense, and thus, the Raman signals from molecules at these sites are particularly strong and contribute to the main fraction of the overall intensity. [ 233,234 ] Because the metal nanostructures can support surface plasmons, [ 235 ] most SERS‐active substrates are based on Ag or Au.…”
Section: Applicationsmentioning
confidence: 99%